2023
DOI: 10.1182/bloodadvances.2022007625
|View full text |Cite
|
Sign up to set email alerts
|

Effects of teclistamab and talquetamab on soluble BCMA levels in patients with relapsed/refractory multiple myeloma

Abstract: B-cell maturation antigen (BCMA) is selectively expressed as a surface protein on plasma cells and is a validated target for multiple myeloma (MM). A soluble form of BCMA (sBCMA) is elevated in the sera of patients with MM. The bispecific antibodies teclistamab (BCMA×CD3) and talquetamab (G protein-coupled receptor family C group 5 member D [GPRC5D]×CD3) are in clinical development as therapies for MM. Using data from patients with relapsed/refractory MM (N=300) who participated in phase 1 studies of teclistam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 22 publications
3
14
0
Order By: Relevance
“…This observation was consistent with other BCMA-targeted therapies and adds value of sBCMA as a marker for response. 16 Moreover, the magnitude of the decrease in sBCMA levels correlated with depth of response.…”
Section: Pd Characteristicsmentioning
confidence: 95%
See 1 more Smart Citation
“…This observation was consistent with other BCMA-targeted therapies and adds value of sBCMA as a marker for response. 16 Moreover, the magnitude of the decrease in sBCMA levels correlated with depth of response.…”
Section: Pd Characteristicsmentioning
confidence: 95%
“…Population PK analysis showed that baseline sBCMA concentration did not significantly impact the PKs of teclistamab, indicating sBCMA is not a sink for teclistamab. 16 Regarding clinical activity, although patients with baseline sBCMA levels up to ~800 ng/mL responded to teclistamab, significantly lower levels of baseline sBCMA were observed in responders compared to nonresponders. 13 This finding is consistent with other reports that showed higher sBCMA levels were associated with poorer clinical outcomes.…”
Section: Pd Characteristicsmentioning
confidence: 98%
“…Its downstream effects lead to the activation of NF‐κB, ETS‐like transcription factor 1 (Elk‐1), c‐jun N‐terminal kinase, and p38, resulting in increased expression of anti‐apoptotic molecules such as Bcl‐2 and Bcl‐XL which support plasma cell survival [20]. Elevated levels of soluble BCMA (sBCMA) are found in the serum of MM patients, correlating with disease burden [21–23]. sBCMA is produced by γ‐secretase, which cleaves BCMA from the cell membrane [24].…”
Section: Which Targets Are Commonly Used In Multiple Myeloma?mentioning
confidence: 99%
“…Teclistamab works by redirecting CD3-positive T cells to MM cells that express BCMA to induce cytotoxicity and tumour cell death [3]. This targeting of BCMA is effective as BCMA is overexpressed and activated in MM [11], and is mediated by the secretion of perforin and certain granzymes from cytotoxic T cells [3]. This process is non-specific and does not involve major histocompatibility complex class 1 molecules on antigen-presenting cells [3].…”
Section: Pharmacodynamicsmentioning
confidence: 99%
“…Reductions in soluble BCMA levels were also seen within one month of treatment [3]. The extent of the reduction was correlated to the depth of patient response, as patients who had achieved complete response (CR) or stringent CR had the greatest reductions from baseline in soluble BCMA levels [11].…”
Section: Pharmacodynamicsmentioning
confidence: 99%